Assessment of the microbiological safety of salad vegetables from different Restaurants in Ilam - Avazpour, Moayed; Rostami Nejad, Mohammad; Seifipour, Fariba; Abdi, Jahangir (Archives of Advances in Biosciences, 2013)
Vegetables, used in preparing salads, are most important part of the diet. These materials are often irrigated by untreated urban wastewater. Wastewater, contaminated with ova of parasites, bacteria and protozoa, are used as fertilizers and it can cause a variety of infectious diseases. The purpose of this study is detection of microbial contamination of salad used in Ilam’s restaurants. In this study, 42 samples were collected from all restaurants placed in Ilam city and transferred to the laboratory. Brilliant Green Medium, Trypton water and Coax reagent used for detection of Escherichia coli. Water broth, Selenit systein, Tetrationat, Salmonella-shigella agar and Briliant green was used for identification of salmonella. For detection of Enterococcus, KF agar medium containing a diphenyl Tetrazolium chloride was used. Sabro dextrose agar medium (SDA) was used for detection of mold and yeast and wet mount and concentration methods used for parasitology investigations. The results of this study indicate that about 66.66% of samples were infected with Enterococcus, 69% had E. coli contamination and 83.33% of samples were contaminated with yeast. Samples were negative for presence of Salmonella and mold (mold not more than 103). Parasites contamination of samples was (4 cases) 9.5% for Giardia lamblia, (10 cases) 23.8% for Taenia eggs, 31% (13 cases) for Hymenolepis nana 16.6% (7 cases) for Entamoeba coli. The results of this study showed that salads are contaminated with infectious agent and the use of appropriate disinfectants and washing the vegetables used in salad preparation is essential for controlling infectious diseases.